PENDAMPINGAN ALIH TEKNOLOGI PADA UKM CANVAS DARI TRADISIONAL KE MODERN - Rini Widianingsih; Triani Arofah; Sri Martini (Jurnal Pengabdian Bisnis dan Akuntansi Soedirman (JPBA), 2022)
By utilizing technology, SMEs can have broad market potential and create a variety of profitable new opportunities. This service focuses on assisting the transfer of technology for Canvas SMEs from traditional to modern, where Canvas SMEs produce various products such as bags, tablecloths, sarungs. pillows etc. The problem faced by these SMEs is that they still use traditional technologies such as manual sewing and manual cutting of materials. Apart from that, another problem is the unfulfillment of product orders in large quantities given the minimum equipment and manpower. The solution offered is meeting the needs for sewing machine equipment and material cutting tools, as well as assisting their use for the UKM workers. The assistance will be carried out in stages over 8 months until the equipment can be used by workers in UKM Canvas. This assistance is expected to increase production capacity and fulfillment customer orders on UKM Canvas.